Love in the Time of Ethnography : Essays on Connection as a Focus and Basis for Research. - Carspecken, Lucinda (Anthropology of Well-Being: Individual, Community, Society., 2017)
In Love in the Time of Ethnography, the contributors argue that research is an affective process as well as a cognitive one. The authors explore love-variously defined-as an important facet of human experience, as a way of knowing and as an ethical rationale for ethnography.